Inhibition of phosphodiesterase 2 reverses gp91phox oxidase-mediated depression- and anxiety-like behavior. (December 2018) - Huang, Xianfeng; Xiaokaiti, Yilixiati; Yang, Junqing; Pan, Jianchun; Li, Zhi; Luria, Victor; Li, Yunfeng; Song, Guoqiang; Zhu, Xiongwei; Zhang, Han-Ting; O'Donnell, James M.; Xu, Ying
Abstract: Phosphodiesterase 2 (PDE2) plays an important role in treatment of stress-related depression through regulation of antioxidant defense and neuroprotective mechanisms. However, the causal relationship between PDE2 and the prevalence of depression and anxiety upon exposure to oxidative stress has not been investigated. The present study examined whether the effects of PDE2 inhibition on oxidative stress were directly involved in reduced ROS by regulating NADPH subunits gp91phox oxidase. The results suggested that the PDE2 inhibitor Bay 60-7550 reversed oxidative stress-induced behavioral signature, i.e. depression and anxiety. Pretreatment with the oxidizing agent DTNB completely blocked, while the reducing agent DTT and the NADPH oxidase inhibitor apocynin potentiated the effects of Bay 60-7550 on behavioral abnormalities, demonstrating the relationship between PDE2 and oxidative stress. Consistently, an in vitro test revealed the positive correlation between ROS and PDE2 levels. Moreover, Bay 60-7550 decreased corticosterone-induced gp91phox expression, which is the source of ROS. The subsequent study suggested that Bay 60-7550 induced decrease in ROS and increase in cAMP/cGMP, pVASP, pCREB, and the neurotrophic factor BDNF levels, which were completely blocked by CRISPR/Cas9-mediated gp91phox overexpression and potentiated by gp91phox siRNA-based antioxidant strategies. The in vivo test in stressed mice further suggested that gp91phox overexpression completely blocked the antidepressant- and anxiolytic-like effects of Bay 60-7550, while gp91phox knockdown enhanced such effects. These results provide solid evidence that the antidepressant- and anxiolytic-like effects of Bay 60-7550 against stress are causally related to down-regulation of gp91phox and activation of the cAMP/cGMP-pVASP-CREB-BDNF signaling pathway.